Religious Teacher Performance: Revitalization of Islamic Religious Education (IRE) Teachers As Innovators - Fitri, Agus Zaenul (Taallum: Jurnal Pendidikan Islam, 2018)
IRE teachers are the spearhead of success in learning religious education at schools. Curriculum changes will not have much impact on the quality of learning, if the quality of teachers is not improved. The strategy taken is to improve the performance and quality work of teachers, because the function of teachers are not only as an educator and facilitator, but also acts as an innovator in education. Innovators are not only means âchanging" but also presents something that is really new and able to make the old things become new existence in context to the present. So innovative teachers are required and have a good performance, not only physically but also responsibility and performance, so as to improve the quality of education and special learning in Islamic religious education. The main performance of teachers from the physical aspects such as appearance and fashion, but far more important is competence in the mastery of learning materials, the ability of managing the class, the authority as education, social interaction and exemplary both at school and in the community. IRE teachers with good performance will not only able to inspire for learners, and even will be able to produce renewal in IRE.